2019
DOI: 10.1016/j.jalgebra.2018.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Cluster algebras and snake modules

Abstract: Snake modules introduced by Mukhin and Young form a family of modules of quantum affine algebras. The aim of this paper is to prove that the Hernandez-Leclerc conjecture about monoidal categorifications of cluster algebras is true for prime snake modules of types A n and B n . We prove that prime snake modules are real. We introduce S-systems consisting of equations satisfied by the q-characters of prime snake modules of types A n and B n . Moreover, we show that every equation in the S-system of type A n (res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…This proves Conjecture 1.2 for snake modules and gives a geometric algorithm for the truncated q-characters. As a slight generalization of Theorem 3.4 of [10], we show in Theorem 4.2 that snake modules are real modules.…”
Section: Snake Modulesmentioning
confidence: 79%
See 4 more Smart Citations
“…This proves Conjecture 1.2 for snake modules and gives a geometric algorithm for the truncated q-characters. As a slight generalization of Theorem 3.4 of [10], we show in Theorem 4.2 that snake modules are real modules.…”
Section: Snake Modulesmentioning
confidence: 79%
“…In [24], they introduced a purely combinatorial method to compute q-characters for snake modules of types A and B, and in [25], they used snake modules to construct extended T -systems for types A and B. In [10], it was shown that all prime snake modules are real and that they correspond to some cluster variables in the cluster algebra constructed by Hernandez and Leclerc. Our first main theorem is the following. This proves Conjecture 1.2 for snake modules and gives a geometric algorithm for the truncated q-characters.…”
Section: Snake Modulesmentioning
confidence: 99%
See 3 more Smart Citations